2018
DOI: 10.1080/14740338.2018.1486820
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reaction reporting in institutions across six Chinese provinces: a cross-sectional study

Abstract: The institutions surveyed have established ADR monitoring systems. However, these systems have flaws. Urgent improvements are needed in funding, basic resources, reporting processes, and other pharmacovigilance activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Jiangsu and Hubei provinces have more developed economies and also more complete regulatory systems for ADR monitoring, which other studies have noted. 22,23) Shaanxi province is a typical representative of the poorer western China provinces, and has worse supervision and policies on ADRs. It therefore seems likely that economic differences and mismatches in regional policy may be the main reasons for the geographical differences in report quality.…”
Section: Discussionmentioning
confidence: 99%
“…Jiangsu and Hubei provinces have more developed economies and also more complete regulatory systems for ADR monitoring, which other studies have noted. 22,23) Shaanxi province is a typical representative of the poorer western China provinces, and has worse supervision and policies on ADRs. It therefore seems likely that economic differences and mismatches in regional policy may be the main reasons for the geographical differences in report quality.…”
Section: Discussionmentioning
confidence: 99%
“…The survey was only developed in English. Potential for reporting bias 31 Rorig and de Oliveira [ 57 ] To evaluate the implementation and operation of the pharmacovigilance programme in the pharmaceutical industry Not reported Brazil Pharmaceutical companies 50 companies Self-administered questionnaire by pharmaceutical companies' PV sector, regulatory affairs sector, or customer support service Not reported 1—Company identification, its origin and the characterisation or absence of a PV programme; 2—Information relating to factors required for PV programme implementation; 3—Pharmacovigilance programme results, and information about notifications reception and how this was treated Not reported 25 Shin et al [ 55 ] To survey the collection and management of adverse effect reports in 21 Asia–Pacific Economic Cooperation (APEC) countries, compare the PV status and systems by country, and finally, to harmonise PV regulation in the APEC region Not reported Asia‐Pacific Economic Cooperation (APEC) region countries National Pharmacovigilance Centre 15 countries: Australia (AU), Brunei (BN), Chile (CL), Indonesia (ID), Malaysia (MY), Mexico (MX), Papua New Guinea (PG), Peru (PE), Philippines (PH), Singapore (SG), Taiwan (TW), Thailand (TH), Japan (JP), South Korea (SK), and the USA Self-administered questionnaires by heads of PV teams from PV agencies Modified WHO Pharmacovigilance Indicators Three domains: Structure, process, and outcome of pharmacovigilance system Not all countries in the region responded to the survey. Did not include all questions and answers from WHO's PV indicators.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies employed self-completion questionnaires for data collection [ 45 , 48 53 , 55 – 57 ], and nine employed mixed-methods [ 37 41 , 43 , 44 , 46 , 47 ] including interviewer-administered questionnaires alongside a documentary review. Two studies [ 42 , 54 ] employed only qualitative methods including interviews and literature or documentary review.…”
Section: Resultsmentioning
confidence: 99%
“…The 2019 Chinese national monitoring report on ADEs recommends that attention be paid to risks of anti‐infective medications, cardiovascular system medications, oncology medications, and medications predominantly used in the elderly 9,10 . Studies have shown that the most frequent manifestations of ADEs are gastrointestinal disorders, skin and subcutaneous tissue disorders, general disorders, and nervous system disorders as reported by pharmaceutical manufacturers, operating companies, and medical institutions 11,12 .…”
Section: Introductionmentioning
confidence: 99%